Impact of Right Ventricular Apical Pacing and Its Frequency on Left Atrial Function - Choi, Byung-Joo (Korean Society of Echocardiography, 2012)
BACKGROUND: Right ventricular apical (RVA) pacing induces left ventricular (LV) dyssynchrony, increases the risk of persistent atrial fibrillation in the long term. The aim was to investigate the effects of RVA pacing on left atrial (LA) function, which are unknown. METHODS: Echocardiographic evaluation including LV dyssynchrony based on conventional Doppler, tissue Doppler imaging and speckle tracking strain echocardiography was done before and after (12 months) single-chamber ventricular pacemaker implantation in 40 patients with sick sinus syndrome. Patients were divided to 2 groups, according to the RVA pacing frequency (group I had higher pacing rate of more than 50% and group II, less than 50%). RESULTS: There was no significant difference in LV ejection fraction, however, mean global LV strain, myocardial performance index, and parameters of LV dyssynchrony had shown significant changes after 12 months of RVA pacing. There were also significant increase in the LA volume index and the reduction of peak systolic LA strain and strain rate (SR), peak early and late diastolic SR after RVA pacing. Moreover, there was significant deterioration of LV dyssynchrony and both LA and LV longitudinal function in even group II. LA functional deterioration and LA volume was significantly correlated with the frequency of RVA pacing. CONCLUSION: LV dyssynchrony, induced by RVA pacing, significantly impaired active LA contraction and passive stretching, and these findings were shown in the patients with even less than 50% of RVA pacing. Impairment of LA strain/SR was significantly correlated with the frequency of RVA pacing.